2020
DOI: 10.1016/j.mcp.2020.101666
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a duplex SYBR green I-based real-time polymerase chain reaction assay for the rapid detection of canine circovirus and canine astrovirus

Abstract: The similar clinical characteristics of canine circovirus (CaCV) and canine astrovirus (CaAstV) infections and high frequency of co-infection make diagnosis difficult. In this study, a duplex SYBR Green I-based real-time polymerase chain reaction (PCR) assay was established for the rapid, simultaneous detection of CaCV and CaAstV. Two pairs of specific primers were designed based on the Rep gene of CaCV and the Cap gene of CaAstV. By using the real-time PCR assay m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Compared with loop-mediated isothermal amplification, the TaqMan-based real-time PCR assay has superior accuracy. Isothermal amplification requires specialised personnel for operation, and the samples are vulnerable to contamination; therefore, the potential for false positive results is high and it is difficult to guarantee the accuracy of detection ( 18 ). Compared with SYBR, the cost of TaqMan assays is higher, where the expense probe synthesis particularly is a consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with loop-mediated isothermal amplification, the TaqMan-based real-time PCR assay has superior accuracy. Isothermal amplification requires specialised personnel for operation, and the samples are vulnerable to contamination; therefore, the potential for false positive results is high and it is difficult to guarantee the accuracy of detection ( 18 ). Compared with SYBR, the cost of TaqMan assays is higher, where the expense probe synthesis particularly is a consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these results showed that circovirus can maintain a certain degree of virulence in feces and can infect other animals through the fecal-oral route. Phylogenetic analysis showed that PCV3 has a close relationship with birds and penguins ( Figure 3 ), which suggests that the transmission mode of circovirus might be similar to that of influenza, in which birds play a crucial role as the intermediate host ( Zhou et al, 2018 ; Karakus et al, 2019 ; Wang et al, 2020 ). However, in this cycle, whether the source of porcine circovirus is directly transmitted by birds and/or wild boars is worthy of further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to these traditional detection methods, real-time uorescence quantitative PCR has great advantages in terms of sensitivity and speci city [33,35], and detects virus even at lower concentrations [36]. In addition, compared with TaqMan-based real-time PCR, the SYBR Green I-based real-time PCR method is cheaper and easier [12].…”
Section: Discussionmentioning
confidence: 99%
“…Canine Circovirus (CaCV) is a single-stranded, non-capsule DNA virus belonging to the circovirus family [12]. It has two ORFs that encode replicase proteins and capsid proteins, respectively [13].…”
mentioning
confidence: 99%